Editorial note - Assounga, Alain (African Journal of Nephrology, 2015)
In this issue of the African Journal of Nephrology (AJN Vol 18, No 1) we publish original articles ranging from the prevalence of chronic kidney disease in an African population in general, to the role of HIV in kidney disease. An elegant study of fractionated heparin use in haemodialysis is also presented. Continuous ambulatory peritoneal dialysis is an important modality of renal replacement to be considered in Africa in view of its ease of operation. However, beware of potential complications including sclerosing peritonitis as reported in Cape Town (South Africa). As in the past, this issue covers a wide variety of topics with contributions from diverse authors from south to west and North Africa. On behalf of the editorial board, I wish to take this opportunity to thank all of the authors and reviewers who have contributed to this issue of the journal, as well as to the readers for their sustained interest in the African Journal of Nephrology. Prof A. Assounga, Editor-in-chief